Comic book paper sculpture/ Hamimy Hashim - Hashim, Hamimy (2011)
Comic book paper sculpture is a 3-dimensional art that can attract viewers to be more involved more in sculptural art. This research study looks at the importance of comic books and the development processes of making comic book paper sculpture artwork. In this study the instruments used in the data gathering process are art-based research from the media, materials, and techniques. This research has explored the use of a variety of materials taken from comic book images and characters. Then the researcher recreated them from two-dimensional to three-dimensional art by using mixed media work. In the end, the research study had shown that the researcher must be encouraged to explore on the use of materials , techniques and creativity more so as to make comic book paper sculpture as the most interesting paper sculpture. The researcher found out that the transfer of ideas, out-of-the-box thinking to visualize form on paper was a process fully artistic creativity and critical thinking. The researcher also tried to experiment and explore the use of different materials to produce artworks. The benefits of this research study toother artists, viewers, students, children and society at large are that they can gain more knowledge, skills and new ideas in making paper sculptures. It is recommended that every researcher embarking on paper sculpturing should try to continue some elements of art in order to obtain more effects into every design project. In conclusion, there is hope for the researcher and future researchers to do more research on paper sculpturing in order to develop a better art product for the future.